Time and income poverty: An interdependent multidimensional poverty approach with German time use diary data - Joachim Merz; Tim Rathjen (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2009)
Income as the traditional one dimensional measure in well-being and poverty analyses is extended in recent studies by a multidimensional poverty concept. Though this is certainly a progress, however, two important aspects are missing: time as an important dimension and the interdependence of the often only separately counted multiple poverty dimensions. Our paper will contribute to both aspects: First, we consider time - and income - both as striking and restricting resources of everyday activities and hence account for time and income as important multiple poverty dimensions. Second, the interdependence of the poverty dimensions will be evaluated by the German population to allow an advanced approach to understand possible substitution effects and the respective trade offs between the dimensions. Referring to the time dimension, we follow Sen's capability approach with its freedom of the living conditions' choice and social exclusion and argue, that restricted time might exclude from social participation. In particular, restricted genuine, personal leisure time (not entire leisure time) in particular is associated with a restricted social participation. The crucial question then is how to measure the substitution between income and such genuine leisure time. In our analysis we consider the country population's valuation with data from the German Socio-Economic Panel and estimate the substitution by a CES-utility function of general utility/satisfaction. Given this quantification we disentangle time, income and interdependent multidimensional poverty regimes characterising the working poor. In addition, we quantify further socio-economic influences for each interdependent multidimensional poverty regime by a multinomial logit based on time use diary data of the German Time Use Study 2001/02. One striking result for Germany: the substitution between time and income is significant and we find an important fraction of time poor who are unable to substitute their time deficit by income. These poor people are ignored within the poverty and well-being as well as the time crunch and time famine discussion so far. – – Einkommen als traditionelles eindimensionales Wohlfahrts- und Armutsmaß wird in neueren Studien um ein multidimensionales Konzept erweitert. Obwohl dies sicherlich ein Fortschritt ist, fehlen zwei wichtige Aspekte: Zeit als eine wichtige Dimension und die Interdependenz der oft nur separat gezählten multiplen Armutsdimensionen. Unsere Studie will zu beiden Aspekten einen Beitrag liefern: erstens, wir betrachten Zeit - und Einkommen - beide als entscheidende und beschränkende Ressourcen aller täglichen Aktivitäten und betrachten deshalb Zeit und Einkommen als wichtige Dimensionen einer multiplen Armutsanalyse. Zweitens, die Interdependenz der multiplen Armutsdimensionen wird durch die Bevölkerung insgesamt bewertet, um zu einem Verständnis möglicher Substitutions- und Austauschbeziehungen zwischen den Dimensionen zu kommen. Hinsichtlich der Zeitdimension folgen wir Sen's Capability-Ansatz mit seiner freien Wahl der Lebensbedingungen und sozialer Exklusion und argumentieren, dass eine Einschränkung der Zeit die soziale Partizipation einschränken kann. Im Besonderen ist eine Beschränkung der persönlichen, genuinen Freizeit (nicht die gesamte Freizeit) verknüpft mit eingeschränkter sozialer Partizipation. Die entscheidende Frage jedoch ist, wie die Substitution zwischen Einkommen und solcher persönlicher Freizeit erfasst werden kann. In unserer Analyse berücksichtigen wir die Bewertung der Bevölkerung mit Daten des Sozio-ökonomischen Panels und schätzen die Substitution mit einer CES-Nutzenfunktion einer generellen Zufriedenheit. Mit dieser Qantifizierung können wir dann singuläre Zeit- und Einkommensarmut sowie erweiterte multiple Armutssektoren für die als arm geltenden Erwerbstätigen (working poor) herausarbeiten. Wir quantifizieren zudem weitere sozio-ökonomische Einflußfaktoren für jede der interdependenten multidimensionalen Armutssektoren mit einem multinomialen logit Ansatz basierend auf den Zeittagebuchdaten der deutschen Zeitbudgeterhebung 2001/02. Ein herausragendes Ergebnis für Deutschland: Substitution zwischen Zeit und Einkommen ist signifikant und wir finden einen hohen Prozentsatz von zeitarmen Menschen, die nicht in der Lage sind, ihr Zeitdefizit durch Einkommen zu substituieren. Dieser Personenkreis wird sowohl in der Armuts- und Wohlfahrtsdiskussion als auch in der Diskussion um Zeitstress und Zeitdruck bisher ignoriert.
Keywords: D31; D13; J22; 330; Interdependent multidimensional time and income poverty; time and income substitution; extended economic well-being; satisfaction; CES utility function estimation; working poor; German Socio-Economic Panel; German Time Use Surveys 2001/02; Interdependente multidimensionale Zeit- und Einkommensarmut; Zeit- und Einkommenssubstitution; erweiterete ökonomische Wohlfahrt; Zufriedenheit; Schätzung einer CES-Nutzenfunktion; arme Erwerbstätige (working poor); Deutsches Sozio-ökonomisches Panel; Deutsche Zeitbudgeterhebunge 2001/02; Armut; Zeitverwendung; Einkommensverteilung; Lebensqualität; Deutschland